(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
E-government for Sustainable Development is one of international cooperation strategy in dealing with environmental protection and ecological problems through enhanced citizen participation, better access and quality of services in order to achieve Green Governments. In this context, some countries are supported by international assistance to achieve this goal with benchmarking and benchlearning approaches. This research contributes to explain the relationship between improvements in governance influences in economic, social and environmental development and how such regional cooperation on the development of national information and communication technology (ICT) strategies and programs is related to E-government and Sustainable Development. This comparative study of Andean countries takes a Rational Neo-institutionalist perspective to look at longitudinal changes in these developing countries. Quantitative data such as E-government index is combined with qualitative information from reports and documents in order to empirically examine effects of e-government on sustainable development in these countries. The findings show that the strategies adopted by Ecuador have significantly contributed to its location within the references in progress of E-government and Sustainable Development in the region. The research suggests that E-government development has positive effects on better governance and sustainable development of Andeans countries. Advancement on E-government is not only a trait of developed countries but also serves as an enabler for sustainable development of developing countries.